Relationship between vitamin B6 intake and thyroid function in US adults: NHANES 2007–2012 results - Lei Li; Jiangbo Wang; Jianping Chen (PLoS ONE, 2025)
Background Existing studies have focused on the relationship between vitamin B6 and thyroid disease. However, there is a lack of large cross-sectional studies reporting on the relationship between vitamin B6 and thyroid function. Therefore, the present study aimed to assess the association between vitamin B6 intake and thyroid function in a population of US adults aged 20 years and older, using data from the National Health and Nutrition Examination Survey (NHANES) between 2007 and 2012. Methods Demographic, dietary, thyroid function, and relevant data from NHANES 2007–2012 were collected. The relationship between vitamin B6 intake and thyroid function was analysed using weighted multiple regression and restricted cubic spline analysis, including subgroup and interaction analysis. Results The study included 6954 participants with a weighted mean age of 47.39  ± 16.60 years, mean vitamin B6 intake of 2.07 ± 1.15 mg, and mean TT4 level of 7.88 ± 1.61 μg/dL. A statistically significant negative correlation was noted between vitamin B6 intake and TT4 levels (β  =  −0.05, 95% CI  =  −0.10 to 0.00, P  =  0.033). In addition to this, subgroup analyses we found: In the gender subgroup, a significant negative correlation was found between vitamin B6 intake and TT4 levels in the male population (β = −0.06, 95% CI  =  −0.11 to −0.01, P  =  0.028); in the age subgroup, a significant negative correlation was found between vitamin B6 intake and TT4 levels in older people aged 60–80 years (β  =  −0. 13, 95% CI  =  −0.23 to −0.04, P  =  0.008); in the BMI subgroup, we found a significant negative correlation between vitamin B6 intake and TT4 levels in overweight people (BMI: 25–29.9 kg/m2) (β  =  −0.13, 95% CI  =  −0.20 to −0.06, P < 0. 001); in the iodine content subgroup, we found a significant negative correlation between vitamin B6 intake and TT4 levels in people with a normal iodine intake (100–299 ug/L) (β  =  −0.07, 95% CI  =  −0.13 to −0.01, P  =  0.021). Finally, in the subgroups of gender, age, BMI, and iodine content, no interaction was found. Conclusions To summarise, we believe that vitamin B6 may reduce serum TT4 levels by inhibiting inflammation.